Structural Design For A Residential Commercial Building Hebron - Ghayyadah, Ahmad; Al Mohtaseb, Mohammed (جامعة بوليتكنك فلسطين - مباني, 2023)
The work of a residential building project was chosen because the city of Hebron and other cities of the West Bank suffers from overcrowding and the scarcity of land allowed for construction due to the occupation’s limitation of the areas allowed for construction, and the division of land into areas (A, B, C). This project aims to create a safe, feasible and economical structural design for a residential building. As the process of distributing columns and studying the behavior of the building under the influence of main and horizontal loads, choosing the best type of knots, walls and foundations, and following the best methods and solutions from an economic and safety point of view, is the main objective of this project. This building consists of 10 floors, with a total area equal to 4456 square meters, and it has 2 staircases in addition to 1 electric elevator. A dam for the warehouse with an area of 400 square meters, and it contains five residential floors with an area of 482 square meters, each floor contains two apartments, It also contains a roof floor, in addition to a floor containing a roof with an area of 236 square meters, and a repeating staircase with an area of 40 square meters.. After the completion of the project, we expect to be able to provide a structural design for all structural elements of the project in accordance with the requirements of the American and Jordanian code. In this project, I will use several engineering programs, namely: 1- AutoCAD. 2- Ater. 3-Safe. 4-SP Column . 5-E Tabs
no of pages 102, مباني 13/2023
Keywords: Structural Designs